2011
DOI: 10.1002/oa.1174
|View full text |Cite
|
Sign up to set email alerts
|

Nonmetric dental characteristics of the early modern population of Okinawa Island in Nansei Islands, Japan

Abstract: Dental morphological characteristics of the early modern population (c. 17-19th century AD) of Okinawa Island, Nansei Islands, were investigated to clarify their genealogical characteristics. We observed and classified 25 nonmetric traits of tooth crowns and roots from human remains (106 individuals) excavated from tombs of the early modern period in Okuma, Ginowan City, Okinawa. The incidences of these traits were compared with the incidences in the populations of the other Nansei Islands, of Japan, and of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Because a differentiation between the Ryukyu and mainland population has also been demonstrated [11], the Amami Islanders are suggested to belong predominantly to the Ryukyu population. Previous dental morphological studies found that the modern inhabitants of Tanegashima Island, just south of Kyushu, are most similar to the mainland Japanese (Figure 1) [24], [25]. Thus, we suggest a genetic boundary between the Amami Islands and Tanegashima Island, which should be further verified (Figure 1).…”
Section: Discussionsupporting
confidence: 58%
“…Because a differentiation between the Ryukyu and mainland population has also been demonstrated [11], the Amami Islanders are suggested to belong predominantly to the Ryukyu population. Previous dental morphological studies found that the modern inhabitants of Tanegashima Island, just south of Kyushu, are most similar to the mainland Japanese (Figure 1) [24], [25]. Thus, we suggest a genetic boundary between the Amami Islands and Tanegashima Island, which should be further verified (Figure 1).…”
Section: Discussionsupporting
confidence: 58%
“…This difference is qualitatively comparable to the facial shift from the Jomon to the modern Japanese in Honshu, and may result from a southward population influx from the main islands of the Japanese archipelago during medieval times (e.g. Asato, 1996;Doi, 2003;Higa et al, 2003;Manabe et al, 2008Manabe et al, , 2011. Nevertheless, the results indicate that the early-modern Okinawans had facial features seen in both Okinawa Jomon/ Yayoi and early-modern Honshu Japanese, as plausibly illustrated by the PCA result ( Figure 6A).…”
Section: Discussionmentioning
confidence: 58%
“…However, both morphological and genetic findings have also emphasized differential traits of the Ryukyuans (including the Okinawans) from the Jomon/Ainu cluster, cautioning against a simple model that regards the modern Ryukyuans as direct descendants of the prehistoric Jomon, and suggesting considerable population influx from surrounding regions into the Ryukyu area during medieval times (Dodo et al, 1998(Dodo et al, , 2000Asato and Doi, 1999;Hatta et al, 1999;Pietrusewsky, 1999Pietrusewsky, , 2004Pietrusewsky, , 2010Higa et al, 2003;Fukumine et al, 2006;Manabe et al, 2008Manabe et al, , 2011. Dodo et al (2000) compared facial skeletons among many Japanese groups from different periods and regions, and found that the early-modern Okinawans did not exhibit some facial characteristics that are manifested in both Jomon and Ainu (e.g.…”
Section: Introductionmentioning
confidence: 99%